2012
DOI: 10.1007/s00392-012-0436-2
|View full text |Cite
|
Sign up to set email alerts
|

Lasting reduction of heart transplant tachycardia with ivabradine is effective and well tolerated: results of 48-month study

Abstract: The safety and efficacy of ivabradine applied in heart transplant (HTx) recipients with permanent sinus tachycardia (PST) has been depicted in previous short-term follow-up studies. We sought to investigate the long-term impact of ivabradine in this patient population. From May to November 2006, 29 HTx recipients with PST, who exhibited either contraindications or intolerance of beta-blocker medication or insufficient heart rate (HR) reduction on beta-blocker treatment, first received oral ivabradine treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 28 publications
3
24
0
1
Order By: Relevance
“…Zhang et al [50] during a 12-week follow-up of patients with HTx and chronic tachycardia demonstrated a significant reduction in HR (22%) after ivabradine treatment. These results were confirmed during a long follow-up [51].…”
Section: Heart Transplantsupporting
confidence: 73%
“…Zhang et al [50] during a 12-week follow-up of patients with HTx and chronic tachycardia demonstrated a significant reduction in HR (22%) after ivabradine treatment. These results were confirmed during a long follow-up [51].…”
Section: Heart Transplantsupporting
confidence: 73%
“…Despite the common occurrence of sinus tachycardia in heart transplant recipients, data regarding heart rate control in this distinct patient cohort are extremely limited 7,8,10,11. Ivabradine is a comparatively new therapeutic agent offering selective reduction of heart rate without the systemic side effects of beta-blockade.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, ivabradine, an I f channel antagonist, regulates pacemaker activity in the sinoatrial node, without the systemic side effects of beta-blocker therapy 79. However, long-term study data examining the association between heart rate and left ventricular mass in heart transplant recipients are insufficient 7,8,10,11. The current follow-up study examines the long-term tolerability, efficacy, safety, and echocardiographically determined effects on left ventricular mass after 36 months of ivabradine therapy in stable patients after heart transplantation presenting with symptomatic sinus tachycardia compared with a matched control group.…”
Section: Introductionmentioning
confidence: 99%
“…Beta-blockers (β-blockers) are the most widely used pre-medication to reduce HR and IV form has faster bioavailability. However, their use is limited due to possible contraindications in certain clinical situations (Tab 1) 17,18 .…”
Section: Pharmacological Interventions To Lower Heart Ratementioning
confidence: 99%